Distal Radial Artery Pressures Predict Angiographic Result and Short‐Term Patency Outcome in Hemodialysis Patients With Juxta‐Anastomotic Inflow Stenosis of Radiocephalic Fistula Undergoing Transradial Angioplasty. Issue 3 (21st January 2013) - Lai, Chi‐Cheng; Fang, Hua‐Chang; Lin, Ching‐Hwung; Mar, Guang‐Yuan; Tseng, Ching‐Jiunn; Liu, Chun‐Peng
Abstract: Distal radial artery pressure (RAP) was observed to be reduced after transradial percutaneous transluminal angioplasty (PTA) on the juxta‐anastomotic venous stenosis of radiocephalic arteriovenous fistula (RCAVF). Distal RAPs are easily obtained from a pressure transducer connected with an introducer retrograde inserted into distal radial artery. The clinical role of distal RAP in the setting of transradial PTA remains unknown. This prospective and observational study aimed to explore the relationship between distal RAPs and clinical outcomes. This study recruited hemodialysis patients with RCAVF juxta‐anastomotic venous stenosis undergoing transradial PTA. RAP‐related variables and procedural data before PTA (pre‐PTA) and after PTA (post‐PTA) were analyzed. The study endpoint was dysfunction‐driven re‐PTA during the 1‐year follow‐up. Overall, 73 PTAs significantly reduced the mean of systolic RAPs from 159.6 ± 41.4 to 108.4 ± 41.5 mm Hg; P < 0.0001. Post‐PTA systolic RAP was associated with angiographic outcome ( P = 0.004) and unassisted patency at 3 months ( P = 0.036), but not at 6, 9, or 12 months ( P > 0.05). The group with angiographically successful PTAs had a significantly lower mean of post‐PTA systolic RAPs compared with that with unsuccessful PTAs (98.4 ± 35.4 vs. 128.7 ± 46.1 mm Hg; P = 0.003). The post‐PTA systolic RAP may be seen as a predictor for 3‐month unassisted patency (AUC = 0.669; P = 0.048). In conclusion, this study provides the RAP profile to help guide transradial PTA on RCAVF juxta‐anastomotic venous stenosis and predict 3‐month unassisted patency in a hemodynamic manner.